Прогнозування коренетвірної здатності стеблових живців яблуні за показниками сезонного росту пагонів - Konopelko, Alla (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2021)
The study involved seven species and cultivars of ornamental apple trees including Malus × floribunda, M. halliana, M. niedzwetzkyana, M. × purpurea, M. × purpurea ‘Ola’, M. × purpurea ‘Royalty’, and M. × purpurea ‘Selkirk’. The average value of increment, average length, and duration of shoots’ growth were determined to characterize the seasonal growth of Malus shoots. The percentages of rooted cuttings, callus formation without roots, and unviable cuttings were registered for each investigated taxon. Statistical analysis was performed in Microsoft Excel 2007 following Zaitsev (1990), and Atramentova & Utevskaya (2014).The total duration of shoots growth of the studied species and varieties ranged from 72 (M. × purpurea ‘Ola’) to 118 days (M. niedzwetzkyana); annual shoots reached a length from 213.75 mm (M. × purpurea) to 448.75 mm (M. niedzwetzkyana); the average increment of shoots ranged from 3.90 mm (M. × purpurea ‘Ola’) to 14.70 mm (M. floribunda).The rooting ability of Malus stem cuttings was limited to a reasonably short period of cutting procedure and depended on the application of biologically active substances, their concentrations, and complexes. The highest rooting rate (33.33 %) was observed in M. × purpurea ‘Ola’ after the treatment of its cuttings by 0.6 % indole-3-butyric acid (IBA) at the end of June. A slightly lower rooting rate (20.00 %) was observed in M. halliana cuttings treated by 0.4 % IBA and M. × purpurea ‘Selkirk’ cuttings treated by Podkorzen AB aqua at the end of June. Finally, 7.69 % of M. × floribunda cuttings were rooted with Podkorzen AB aqua at the beginning of July.The prediction of the rooting ability of Malus stem cuttings was confirmed by a strong negative correlation between the percentage of rooted cuttings and the duration of shoots’ growth (r = –0.88). Hence, the percentage of rooted cuttings increases with decreasing duration of shoots growth, depending on the genotype.